2012
DOI: 10.1080/15421406.2012.701845
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Mechanical Characterization of Tack-free Surfaced CSR/Epoxy Adhesive Films

Abstract: High performance epoxy systems have been widely used in electronic devices, aerospace structures, and automotive parts. In this study, introduction of both core-shell rubber (CSR) and thermoplastics into epoxy systems was considered to improve mechanical properties as well as to make tack-free surfaced epoxy films. CSR particles were very uniformly dispersed into epoxy by means of ultrasonic dismembrator and homogenizer at the presence of polymeric dispersion agent. Well-dispersed CSR containing epoxy systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Several authors reported by transmission electron microscopy (TEM) [13,17,18], scanning electron microscope (SEM) [12,18] or atomic force microscopy (AFM) [19], that this kind of fillers lead to a regular distribution of nanodomains. It was also shown that the nanoparticles filled epoxy had their toughness improved [20], as well as their impact resistance [21].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several authors reported by transmission electron microscopy (TEM) [13,17,18], scanning electron microscope (SEM) [12,18] or atomic force microscopy (AFM) [19], that this kind of fillers lead to a regular distribution of nanodomains. It was also shown that the nanoparticles filled epoxy had their toughness improved [20], as well as their impact resistance [21].…”
Section: Introductionmentioning
confidence: 98%
“…Toughened epoxyamine adhesives exhibit an even higher debonding energy [21], mainly due to an increase of viscoelastic dissipation. Many adhesive tests, classified in three categories following the solicitation mode (I, II or III) are used to quantify the total debonding energy [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, conventional studies on CSR nanoparticle/epoxy composite polymers have mainly considered the mechanical properties at room temperature. A number of studies have characterized the properties of the CSR/epoxy at cryogenic temperatures (at 77 K under LN 2 ambient conditions) [ 38 , 39 ] and low temperatures (from −109 to 20 °C) [ 40 , 41 , 42 ], but these studies are rare. Nevertheless, this temperature range is only a partial intersection of the operating temperature range required for the automotive industry, which presents insufficient information for structural adhesive manufacturing.…”
Section: Introductionmentioning
confidence: 99%